ESTUDO DA REAÇÃO DE REDUÇÃO DE OXIGÊNIO CATALISADA POR COMPLEXOS TETRAAZAMACROCICLOS COM DIFERENTES CENTROS METÁLICOS: UMA ABORDAGEM TEÓRICA - Sousa, Natanael de Sousa (2013)
In the present work it was made a theoretical quantum study in level DFT, being used the program Gaussian 09, to verify parameters as: distances and bond angles, electronic configuration, interaction energy and vibrational frequencies for the compounds dibenzotetraaza[14]anulele of first transition line metals MII(DBTAA), and their different spin states, to verify their catalytic potential front the oxygen reduction reaction. Used the basis sets B3LYP with Lanl2DZ, used for transition metals and 6- 31G*, for others atoms. Calculations showed that compounds of Ti, V and Cr come stable in high-spin, while Mn and Fe in Spin middleman and Co, Ni, Cu and Zn in low-spin. Interaction energy and gap HOMO-LUMO were performed, which show that stability increases with atomic number of the metal, in agreement with the Irving-Williams s series, presenting Ni(DBTAA) as stableer and Ti(DBTAA) as the more reagent of the group.